PRIMARY TEACHERS AND CULTURAL – BASED ENGLISH TEXTBOOKS; VOICES, ISSUES, AND DEMANDS - Hikmawati, Agci; Handayani, Rindu (International Journal of Indonesian Education and Teaching (IJIET), 2020)
Teachers and textbooks are two significant success factors in achieving a better standard of education. However, teaching English can be rectified if the teachers only depend on the existing materials without noticing the needs of the students. This study attempted to seek for issues as well as solutions in overcoming teachers’ difficulties in a primary school of SD N 13 Koba, Bangka Regency, Bangka Belitung Province. Two teachers were involved in the study to be interviewed and as the sources of the data. The results of the interview reveal that indeed teachers at this primary school faced issues in teaching English such as their limited knowledge of English, insufficient English teaching times and unprepared more qualified teachers. As for the solution, providing them with lively cultural-based English textbook is one of the ways. As the rule makers, governments could provide more fees to the teachers and add research funds so that researchers are motivated to conduct better and larger scale of areas and participants.DOI: 10.24071/ijiet.2020.040111